Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Catalytic hydrogenation of 2-butyne-1,4-diol: activity, selectivity and kinetics studies - Rode, Chandrashekhar V. (Journal of the Japan Petroleum Institute, 2008)
The reaction pathway for hydrogenation of 2-butyne-1,4-diol involves parallel and consecutive isomerization as well as hydrogenation reactions forming other side products along with cis-2-butene-1,4-diol and butane-1,4-diol. Hence, achieving the highest selectivity to butene- and/or butanediol is critical from industrial point of view. Hydrogenation of butynediol is also of fundamental significance, due to its adsorption characteristics leading to the formation of active species and their role in determining the product distribution. Studies on designing various catalyst systems including colloidal as well supported palladium nanoparticles for the hydrogenation of butynediol, role of additives, catalyst pretreatment, kinetic studies carried out in our group has been presented in this review. Interestingly, almost complete selectivity to the intermediate olefinic diol was achieved with 1% Pd/CaCO3-NH3 catalyst system. This could be due to the competitive adsorption of ammonia on the palladium surface along with the substrate 2-butyne-1,4-diol. Studies on catalyst pretreatment and kinetics using palladium catalyst have also been presented here. Nanostructure palladium both colloidal as well as supported catalysts showed a very high catalytic activity (10-40 times more) in the hydrogenation 2-butyne-1,4-diol to cis-2-butene-1,4-diol compared with the corresponding conventional Pd catalysts. For platinum based catalysts, formation of side products was completely eliminated in the hydrogenation of butyne diol. The increase in the basic strength of alkali metal doped Pt catalysts measured by CO2-TPD, led to the increase in electron density of Pt hence, faster desorption and higher selectivity to butenediol. In the case of continuous hydrogenation, the selectivity pattern was completely different from that found in the case of batch slurry reactor and by varying the contact time, the selectivity to both butene- and butanediols could be varied over a wide range of conditions.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; catalyst pretreatment; nano palladium catalyst; Selective hydrogenation

Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Control of competing hydrogenation of phenylhydroxylamine to aniline in a single-step hydrogenation of nitrobenzene to p-aminophenol - Nadgeri, Jayprakash M.; Biradar, Narayan S.; Patil, Priyanka B.; Jadkar, Sachin T.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2011)
Two steps involving catalytic hydrogenation of nitrobenzene to phenylhydroxylamine (PHA) in acid medium and its rearrangement to p-aminophenol (PAP) were studied separately in a batch reactor, using a well-characterized 3% Pt/C catalyst. The first step of hydrogenation of nitrobenzene to PHA could be carried out at 303 K and a H(2) pressure of 0.69 MPa with complete conversion of nitrobenzene, while the achieved selectivity to PHA was higher than 90% with some formation of aniline, even at lower temperature. The second step of PHA rearrangement to PAP could be achieved under a hydrogen atmosphere at elevated temperature of 353 K to give a maximum selectivity to PAP of 74%.

Continuous dehydration and hydrogenolysis of glycerol over non-chromium copper catalyst: laboratory-scale process studies - Mane, Rasika B.; Rode, Chandrashekhar V. (Organic Process Research & Development, 2012)
A non-chromium Cu:Al catalyst was developed for glycerol dehydration under N-2 atmosphere to acetol and hydrogenolysis to 1,2-propanediol (1,2-PDO). Among the various copper-based catalysts screened in this work, Cu:Al-1 catalyst showed the highest activity and acetol selectivity in water medium, whereas transfer hydrogenation in 2-propanol as the reaction medium led to the formation of 1,2-PDO (10-38%). The same catalyst was also found to catalyze the direct hydrogenolysis of glycerol to 1,2-PDO. Time on stream activity (TOS) of our Cu:Al-1 catalyst for both continuous dehydration and hydrogenolysis of glycerol was found to be 400 h with an average glycerol conversion of 90% and 65%, respectively. Maximum acetol selectivity was 55% while 1,2-PDO selectivity was 91% in dehydration and hydrogenolysis reactions separately. Effects of various reaction conditions on conversion, selectivity, and global rates of the two processes were also investigated.

Cu-ZrO2 nanocomposite catalyst for selective hydrogenation of levulinic acid and its ester to gamma-valerolactone - Hengne, Amol M.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Several copper based catalysts were prepared, characterized and evaluated for the hydrogenation of levulinic acid and its methyl ester. Among these, nanocomposites of Cu-ZrO2 and Cu-Al2O3 quantitatively catalyzed the hydrogenation of levulinic acid and its methyl ester to give 90-100% selectivity to gamma-valerolactone in methanol and water respectively. Both the Cu-ZrO2 and Cu-Al2O3 nanocomposites were prepared by the co-precipitation method using mixed precursors under controlled conditions. XRD results showed that the main active phase of the reduced Cu-ZrO2 catalyst was metallic copper and particle size was found to be of 10-14 nm by HRTEM. The active metal leaching was at a maximum for the Cu-Al2O3 catalyst in a water medium due to the formation of a copper-carboxylate complex that was blue in colour. Surprisingly, copper leaching was completely suppressed in the case of the Cu-ZrO2 catalyst in methanol in spite of the substrate loading was increased from 5 to 20% w/w. The excellent recyclability of the Cu-ZrO2 catalyst with complete LA conversion and > 90% GVL selectivity makes it a sustainable process having a commercial potential.

Cascade synthesis of 2-cyanoacrylamides through deacetalization and/or knoevenagelcondensation followed by selective monohydration of acetals and aldehydes over solid acidferrites - Kamble, Sumit B.; Rode, Chandrashekhar V. (Chemcatchem, 2016)
A new protocol of cascade synthesis for biologically active 2-cyanoacrylamides (1) was developed. The reaction proceeds over a novel magnetically retrievable solid-acid composite of iron oxide, poly(vinylpyrrolidone) and phosphotungstic acid (Fe3O4/PVP-PWA) in AcOH-H2O medium under reflux conditions. This transformation is facilitated through single-site Bronsted acid catalyzed cascade reactions involving deacetalization and/or Knoevenagel condensation followed by selective monohydration of nitriles starting from acetals (5) and aldehydes (2) with malononitrile (3). A series of aldehydes, dimethyl and diethyl acetals, along with some heterocyclic aldehydes were successfully transformed to 2-cyanoacrylamides with >95% yields. TEM images confirmed the coating of the PVP over nanosized Fe3O4. Stereoselective monohydration of 2-benzylidenemalononitriles (4) to E isomers was demonstrated by NOESY experiments. The catalyst could be efficiently recycled seven times on employment of both acetals and aldehydes as substrates, as a result of its magnetic nature.

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Catalytic ozonation of clofibric acid over copper-based catalysts: in situ ATR-IR studies - Sable, Shailesh S.; Ghute, P. P.; Fakhrnasova, D.; Mane, R. B.; Rode, Chandrashekhar V.; Medina, F.; Contreras, S. (Applied Catalysis B-Environmental, 2017)
The current study describes the catalytic ozonation of clofibric acid (CFA) under ambient conditions using copper oxide catalysts synthesized by different methods. The objective of this study is to provide novel catalysts and reaction mechanism for the degradation of emerging pharmaceutical compounds in aqueous solution. Among the various Cu catalysts screened in this study, the Cut-Ali oxide catalyst showed an excellent activity and stability in the degradation and mineralization of CFA. In situ attenuated total reflection IR (ATR-IR) spectroscopy was used to examine the interaction of ozone with the active sites of the catalyst in presence of water and to investigate the possible catalytic mechanism. The presence of Lewis acid sites in the Cut-Ali catalyst increased the amount of chemisorbed water enhancing stronger interaction of ozone to form surface activated species, resulting in higher catalytic activity. The results obtained from in-situ ATR-IR study indicate that surface hydroxyl groups and Lewis acid sites are responsible for promoting the generation of hydroxyl radicals (OHS) from aqueous ozone. (C) 2017 Elsevier B.V. All rights reserved.

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Conversion of benzyl phenyl ether to monoaromatics in high-temperature aqueous ethanol solution under high-pressure carbon dioxide conditions - Taniguchi, Kenkichi; Kusumawati, Etty N.; Nanao, Hidetaka; Rode, Chandrashekhar V.; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (New Journal of Chemistry, 2023)
Solvolysis of benzyl phenyl ether (BPE), which is a model compound of lignin ether linkage, was studied in an aqueous ethanol solution, which can be obtained from bioethanol, under high-pressure carbon dioxide conditions. A batch study revealed that BPE solvolysis to monoaromatics (benzyl ethyl ether (BEE), benzyl alcohol (BA), and phenol (Ph)) proceeded in aqueous ethanol solution over 523 K and the addition of high-pressure carbon dioxide enhanced the initial solvolysis rate and suppressed the side reaction (hydrogenolysis to toluene (TL)). The ethanol molar fraction (ethanol-water volume ratio) is the key factor for the solvolysis reaction, and the highest monoaromatic yield of 72.9% (BEE 10.7%, BA 19.3%, Ph 37.9%, and TL 5.1%) was obtained in aqueous ethanol solution (2 cm(3) : 1 cm(3) = water:ethanol) at 598 K for 3 h under a pressure of 18 MPa of carbon dioxide. The solvolysis reaction proceeded continuously to produce monoaromatics with a flow system. A monoaromatic yield of 76.7% (BEE 8.6%, BA 19.7%, Ph 39.6%, and TL 8.9%) was obtained, and the formation rates were 2.7 x 10(-4) mmol min(-1) for BEE, 6.2 x 10(-4) mmol min(-1) for BA, and 12.4 x 10(-4) mmol min(-1) for Ph at 598 K under flowing water (26 mmol min(-1)), ethanol solution (4.1 mmol min(-1)), carbon dioxide (1.2 mmol min(-1)), and BPE (15.6 x 10(-4) mmol min(-1)) under a total pressure of 40 MPa.